Interspinous bursa and spinal instability - Wichien Laohacharoensombat (2018)
Study design : This is a prospective study. Interspinous tissue was taken intraoperatively for pathological examination for the presence of bursa. The pathologist was unaware of the X-ray findings in each specimen. The presence of bursa was then correlated with X-ray evidence of hypermobility in each segment. Objective : To verify the pathogenesis of interspinous bursal formation. Summary of background data : Interspinous bursa is common in the older population. It has been associated with degenerative lumbar diseases, aging and anatomical distance between the spinous process. However, no detailed exploration of the segmental instability as a cause of bursal formation has been done. Method : The insterspinous tissue was taken intraoperatively from patients diagnosed as multilevelled spinal stenosis who underwent extensive decompression, fusion and instrumentation. The specimens were examined by the same pathologist for the existence of bursa. The presence of bursa was correlated with X-ray motion study of each spinal segment by student /-test. Results : The existence of bursal was significantly correlated with angular mobility of more than 10° Conclusion : Angular mobility is a possible cause of interspinous bursa. On the contrary, the presence of insterspinous bursa may be evidence of segmental hypermobility.